2016
DOI: 10.1209/0295-5075/113/18007
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer network decoding versatility and trust

Abstract: In the recent years, the multilayer networks have increasingly been realized as a more realistic framework to understand emergent physical phenomena in complex real world systems. We analyze a massive time-varying social data drawn from the largest film industry of the world under multilayer network framework. The framework enables us to evaluate the versatility of actors, which turns out to be an intrinsic property of lead actors. Versatility in dimers suggests that working with different types of nodes are m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…To assess the functional importance of these weak ties, we investigated the characteristic properties of the end nodes of these weak ties. Unlike social networks where the end nodes of weak ties are low degree nodes (Sarkar et al 2016), in the sporulation networks of SK1, the nodes forming weak ties were high degree nodes. An example of this was BAS1, a Mybrelated transcription factor involved in amino acid metabolism and meiosis (Mieczkowski et al 2006).…”
Section: Local Properties Of Longitudinal Regulatory Network Of Sk1 mentioning
confidence: 98%
“…To assess the functional importance of these weak ties, we investigated the characteristic properties of the end nodes of these weak ties. Unlike social networks where the end nodes of weak ties are low degree nodes (Sarkar et al 2016), in the sporulation networks of SK1, the nodes forming weak ties were high degree nodes. An example of this was BAS1, a Mybrelated transcription factor involved in amino acid metabolism and meiosis (Mieczkowski et al 2006).…”
Section: Local Properties Of Longitudinal Regulatory Network Of Sk1 mentioning
confidence: 98%
“…It has also been shown that introduction of weights enhances the complete synchronization of identical dynamical units in scale-free networks [75]. Furthermore, recently it has been realised that many real-world complex systems having different types of interactions can be modeled using multiplex or multilayer networks framework [76][77][78]. Motivated from the success of this new framework in predicting various behaviours of interacting units, spectra of adjacency and Laplacian matrices have also been investigated, particularly in the context of understanding occurrence of extreme events [79] and diffusion processes [80] on multilayer networks.…”
Section: Conclusion and Other Directionsmentioning
confidence: 99%
“…Multiplex networks ( Fig. 1) are defined as a collection of two or more layers which share the same nodes but have different connectivities in each layer [12]. Thus they describe networks which possess more than one type of interaction within the same elements, such as transport networks (with different means of travel as different layers), biochemical networks (with different signaling channels representing different layers), etc.…”
Section: Introductionmentioning
confidence: 99%